1978
DOI: 10.1126/science.663634
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Status of Working-Class Children Adopted Early into Upper-Middle-Class Families

Abstract: Failure rates observed (13 +/- 6 percent for school failures, 17 +/- 5 percent for scores below 95 on a collective IQ test) were far below those expected from the social class of birth (55 percent, 51 percent) or observed in a control group (56 +/- 8 percent, 49 +/- 9 percent) but close to those expected from the social class of adoption (15 percent, 15 percent).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
1

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(47 citation statements)
references
References 3 publications
1
45
0
1
Order By: Relevance
“…In addition, they were (iv) aged 4-6 at the time of the adoptive placement; and (v) aged 11-18 and being raised by the two adoptive parents at the time of the second psychometric test. The procedure followed was identical to that used in previous French studies (12,14,22). It was approved by the French Ministry of Health, French Ministry of Education, and the National Association of Adoptive Homes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they were (iv) aged 4-6 at the time of the adoptive placement; and (v) aged 11-18 and being raised by the two adoptive parents at the time of the second psychometric test. The procedure followed was identical to that used in previous French studies (12,14,22). It was approved by the French Ministry of Health, French Ministry of Education, and the National Association of Adoptive Homes.…”
Section: Methodsmentioning
confidence: 99%
“…Second, assuming that there is a sensitive period for learning during early childhood, to what extent can adverse experiences during the first years of life lead to irreversible intellectual impairment, even when experiences during middle and later childhood are positive? Third, although adoption studies have shown an increase in IQ for children born to low SES parents and adopted early by middle or upper SES families (10)(11)(12)(13)(14), no study has demonstrated that adoption after early childhood by middle or upper SES families leads to IQ gains dependent on SES for children with borderline IQs (Ͻ86).…”
mentioning
confidence: 99%
“…For example, some studies have looked at how identical twins' IQs differ after being separated at birth. These studies have been generally dismissed due to very small samples, and typically have examined class rather than race differences (Schiff et al 1978). A similar line of research that uses much larger samples is Elsie Moore's (1986) analysis of differences between Black children adopted into middle-class White homes and Black children adopted into middle-class Black homes.…”
Section: Geneticsmentioning
confidence: 99%
“…In another study from France, Schiff et al (11) reported on 32 children abandoned at birth by their impoverished parents and adopted into homes of upper-middle-class families. The adopted children were compared with 20 biological siblings, who remained with their biological mother.…”
mentioning
confidence: 99%